PENGARUH PANDEMI DAN PENGANGGURAN TERHADAP PERTUMBUHAN EKONOMI DI KOTA BANDA ACEH - Armanda Butar Butar (Lembaga Riset dan Inovasi Kreyat Center, 2023)
This research aims to determine the impact of the COVID-19 pandemic and the unemployment rate on economic growth in the city of Banda Aceh. The influence of the pandemic and unemployment are indicators of the influence of economic growth. This research discusses the influence of the pandemic and unemployment on economic growth in the city of Banda Aceh. The research aims to see and assume how big the level of pandemic and unemployment is in the city of Banda Aceh and how big the decline in economic growth was at the beginning of 2020, especially during the COVID-19 pandemic. This research was written using a quantitative and secondary research approach. The results of the analysis show that economic growth in the city of Banda Aceh can be measured through the increase or decrease in gross domestic product (GRDP) produced by a region because the indicator related to the number of unemployed is GRDP. During the Covid-19 pandemic, economic growth in the city of Banda Aceh experienced a decline. The slowdown in economic growth when the coronavirus outbreak hit was 3.29% (year on year). Meanwhile, unemployment increased by 9.54% due to layoffs during the Covid-19 pandemic. With the COVID-19 pandemic, there has been a decline in the level of economic growth, so the unemployment rate in the city of Banda Aceh has also increased.